The dopamine transporter antagonist vanoxerine inhibits G9a and suppresses cancer stem cell functions in colon tumors - Bergin, Christopher; Zouggar, Aïcha; Mendes da Silva, Amanda; Fenouil, Tanguy; Haebe, Joshua; Masibag, Angelique; Agrawal, Gautam; Shah, Muhammad; Sandouka, Tamara; Tiberi, Mario; Auer, Rebecca; Ardolino, Michele; et al. (Université d'Ottawa | University of Ottawa, 2024)
Cancer stem cells (CSCs), functionally characterized by self-renewal and tumor-initiating activity, contribute to decreased tumor immunogenicity, while fostering tumor growth and metastasis. Targeting G9a histone methyltransferase (HMTase) effectively blocks CSC functions in colorectal tumors by altering pluripotent-like molecular networks; however, existing molecules directly targeting G9a HMTase activity failed to reach clinical stages due to safety concerns. Using a stem cell-based phenotypic drug-screening pipeline, we identified the dopamine transporter (DAT) antagonist vanoxerine, a compound with previously demonstrated clinical safety, as a cancer-specific downregulator of G9a expression. Here we show that gene silencing and chemical antagonism of DAT impede colorectal CSC functions by repressing G9a expression. Antagonizing DAT also enhanced tumor lymphocytic infiltration by activating endogenous transposable elements and type-I interferon response. Our study unveils the direct implication of the DAT-G9a axis in the maintenance of CSC populations and an approach to improve antitumor immune response in colon tumors.
Keywords: Colorectal Cancer; Colon Cancer; Cancer Stem Cells; Epigenetics; Phenotypic Screening; Dopamine Transporter; G9a; EHMT2; DAT; Vanoxerine; GBR-12909